Modeling of Feedstock Formability to Optimize Mold Design and Prevent Possible Defects During Metal Injection Molding - Anatoly Kutsbakh; Alexander Muranov; Alexey Pervushin; Alexey Semenov (Journal of Manufacturing and Materials Processing)
Metal injection molding (MIM) is a current technology used to produce products with complex shapes. Despite the accumulated worldwide experience in using this technology, manufacturers sometimes fail to launch new products of proper quality. Often, this is because defects can occur at the casting stage, the prevention of which is impossible through the use of standard design and technological solutions of molds design and the experimental selection of technological modes. This study aimed to analyze the causes of such defects in the green part and optimize the mold design to ensure defect-free casting, which was impossible for the manufacturer using standard solutions. The core method used in this study was simulation modeling of the casting process. A hypotheses were selected, and an analysis of the causes of defect occurrence in casting was conducted. Simulation modeling proved that defect occurrence was due to the formation of a free melt jet and subsequent air capture by this jet. Based on modeling, different gating and feeding system designs were analyzed, which made it possible to choose a variant that provided the uniform filling of gating cavities without forming jet flows and defects. The novelty of this study lies in its optimization of the mold design to prevent free melt jetting and similar defects in other MIM products by modeling feedstock molding processes. The presented results can help enrich the knowledge base of the mold design for MIM and ensure defect-free production.